- x^2-4x+4=0

y^2-9y+18=0x>yx< yX≥Yx≤yX=Y or no relationOption B

1. x^2-4x+4=0

x^2-2x-2x+4=0

x=2,2

2. y^2-9y+18=0

y^2-6y-3y+18=0

y=6,3 - x^2-x-12=0

y^2-y-6=0x>yx< yX≥YX≤YX=Y or no relationOption E

1. x^2-x-12=0

x^2-4x+3x-12=0

x=4,-3

2. y^2-y-6=0

y^2-3y+2y-6=0

y=3,-2 - x^2+7x+10=0

y^2+12y=35=0x>yx< yX≥YX≤YX=Y or no relationOption C

1. x^+7x+10=0

x^2+5x+2x+10=0

x= -5,-2

2. y^2+12y+35=0

y^2+7y+5y+35=0

y= -7,-5 - 25x^2=625

y^2-10y+25=0x>yx< yX≥YX≤YX=Y or no relationOption D

1. 25x^2=625

x=+5,-5

2. y^2-10y+25=0

y^2-5y-5y+25=0

y=5,5 - x^2-x-42=0

2y^2-8y+8=0x>yx< yX≥YX≤YX=Y or no relationOption E

1. x^2-x-42=0

x^2-7x+6x-42=0

x=7,-6

2. 2y^2-8y+8=0

2y^2-4y-4y+8=0

2y=4,4

y=2,2 - x^4=256

y^2-12y+36=0x>yx< yX≥YX≤YX=Y or no relationOption B

1. x^4=256

x=+4,-4

2. y^-12y+36=0

y^2-6y-6y+36=0

y=6,6 - 2x+3y=3

3x+5y=2x>yx< yX≥YX≤YX=Y or no relationOption A

1. 2x+3y=3……..(1)

3x+5y=2………..(2)

solving euations (1) and (2) we get,

5(2x+3y=3)=10x+15y=15

3(3x+5y=2)=9x+15y=6

x=9

by putting x=9, in equation(1) we get,

18+3y=3

y=-5 - 3x^2-7x+4=0

4y^2-13y+9=0x>yx< yX≥YX≤YX=Y or no relationOption E

1. 3x^2-4x-3x+4=0

3x=4,4

x=4/3, 4/3

2. 4y^2-13y+9=0

4y^2-9y-4y+9=0

4y=9,4

y=9/4, 1 - x^2=16

y^2+6y+8=0x>yx< yX≥YX≤YX=Y or no relationOption E

1. x^2=16

x=4,-4

2. y^2+6y+8=0

y^2+4y+2y+8=0

y= -4,-2 - 5x^2-8x+3=0

2y^2-16y+32=0

x>yx< yX≥YX≤YX=Y or no relationOption B

1. 5x^2-8x+3=0

5x^2-5x-3x+3=0

5x=1, 3/5

2. 2y^2-16y+32=0

2y^2-8y-8y+32=0

2y=8,8

y=4,4

### Click here for topic wise Quantitative Aptitude Questions